Time to Forget "Just-in-Time"? Observations on a visit to Japan - Westbrook, R (1988)
The study of Japanese manufacture continues to focus on certain elements of the JIT/kanban approach. A recent study tour found that these elements might be broadened to include planning systems and people development initiatives, examples of which are described. The degree to which JIT is a system at all, or has been fully understood in the West, is considered and future research directions proposed.